Beyond True Crime: Race, Class, and Institutional Failure in Netflix’s Monster: The Jeffrey Dahmer Story - Amalia, Shabrina Nur; Sujiwa, Krisna; Prihatika, Yusrina Dinar (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2025)
This study explores Netflix’s Monster: The Jeffrey Dahmer Story (2022) by using the theories of Intersectionality and Post-National American Studies to understand how racism, class inequality, and institutional failure are shown in the series. The research aims to examine how the show reflects real social problems in American society, especially the unfair treatment of Black, queer, and immigrant communities. The problem addressed in this study is the lack of academic discussion about how true crime stories can reveal deeper issues of social injustice. Using a qualitative method with content analysis, this research analyzes selected episodes and scenes that show how race, class, gender, and citizenship influence the way victims are represented and treated by institutions. The theory of Intersectionality helps explain how different identities overlap to create multiple forms of discrimination, while Post-National Approach provides perspective to criticize the idea of American exceptionalism. The findings show that the series portrays strong examples of racial bias, class prejudice, and neglect from law enforcement, where the voices of Black women and other minorities are often ignored or doubted. The show also reveals how the media tends to sympathize with white perpetrators while minimizing the suffering of minority victims. In conclusion, Monster: The Jeffrey Dahmer Story is not only a retelling of a true crime case but also a reflection of structural problems in the American justice system, showing how inequality and institutional failure continue to affect vulnerable groups in society.